Application Design to Calculate Employee Salary In Truth And Calculus Table Learning - Fanny Ramadhani; Dimas Prayoga; Ravindra Singh; Dina Aulia; Ayu Sekar (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
Informatics logic is a compulsory subject students especially in propositional calculus material. Proposition calculus is generally studied by various groups of students, from high school to college level. Proposition calculus studies the true (True / False) value of a proposition. Truth table is a tool or table used to provide values with certain rules. The truth table is a table used to see the truth value of a premise / statement. To complete a proposition truth table, we must first find out how many different statements the table contains. This step is absolutely necessary so that there are no errors in solving the problem. Therefore, the authors are interested in making an application for calculating employee salaries with the culpulus proposition method and truth tables that can be used to solve the problem of working on propositions manually, so as to produce accurate truth values. , which at the same time can be used as a medium for student learning